Pengaruh Promosi Kesehatan terhadap Tingkat Pengetahuan Remaja tentang Bahaya Infeksi Menular Seksual di Kelas X IPS SMAN 3 Kota Palangka Raya: The Effect of Health Promotion on the Knowledge Level of Teenagers Regarding the Dangers of Sexually Transmitted Infections in First-Year Students of Social Science, SMAN 3 Palangka Raya - Nasthasya Magdalena; Lensi Natalia Tambunan; Eva Prilelli Baringbing (Jurnal Surya Medika (JSM), 2022)
Sexually transmitted infections (STI) are infections caused by germs such as fungi, viruses, and parasites that enter and multiply in the body and are transmitted through sexual intercourse. Information on reproductive health influences the teenager’s sexual life. STIs can cause many physical, psychosocial, and financial negative impacts. Lack of information on reproductive health, both from parents and schools, determines the level of knowledge of teenagers about STIs. The purpose: The purpose of the study was to determine the effect of health promotion on the knowledge level of teenagers regarding the dangers of sexually transmitted infections. This study uses a pre-experimental design, which the type of design is one group pretest-post-test. The number of samples used in this study is 53 respondents, namely the first-year students of SMAN 3 Palangka Raya. The sampling method used is purposive sampling using inclusion criteria. Meanwhile, the data analysis used paired samples T-test. The result of the paired samples T-test is P value = 0.000 <0.05, which means there is an effect. The conclusion of this study is that there is an effect between health promotion on knowledge and the incidence of sexually transmitted infections. The suggestion that can be given by the author is to utilize teenage health counseling programs to escalate knowledge and understanding of reproductive health.